Odpowiedzi

2009-12-29T16:39:04+01:00
A)
aub=(-∞,10>
a^b=(-3,5>
a\b=(-∞,-3>
b\a=(-3,5)
b)
aub=<-4,∞)
a^b=(2,4>
a\b=(2,4>
b\a=(4,∞)
c)
aub=<-8,10>
a^b=(-3,3>
a\b=<-8,-3>u(3,10>
b\a=Ф (zbiór pusty)

Pozdrawiam :)
2009-12-29T16:43:39+01:00
A) a=(-oo:5> b=(-3:10>
B) a=<-4:4> b=(2:oo)
C) a=<-8:10> b=(-3:3>

A)
AuB = (-∞,10>
B^A = (-3,5>
A\B = (-∞,-3>
B\A = (-3,5)


B)
AuB = <-4,∞)
B^A = (2,4>
A\B = (2,4>
B\A = (4,∞)


C)
AuB = <-8,10>
B^A = (-3,3>
A\B = <-8,-3>
B\A = Ф
2009-12-29T19:35:42+01:00
A)
AuB = (-∞,10>
B^A = (-3,5>
A\B = (-∞,-3>
B\A = (-3,5)


B)
AuB = <-4,∞)
B^A = (2,4>
A\B = (2,4>
B\A = (4,∞)


C)
AuB = <-8,10>
B^A = (-3,3>
A\B = <-8,-3>
B\A = Ф